Mekanisme Penilaian Pemberian Kredit Dalam Meminimalisir Risiko Kredit Pada Bank BJB KCP Mojokerto - Tarissa Seshita Hadi; R. Yuniardi Rusdianto (Journal of Management and Social Sciences, 2024)
Bank BJB KCP Mojokerto which is located on Jl Majapahit No. 333C-333D, Kranggan, Mojokerto City is one of the banks that provides credit facilities for the public. This research aims to determine the credit assessment mechanism of Bank BJB KCP Mojokerto in minimizing credit risk. This research uses qualitative methods with observation, interview and documentation techniques. The research results show that bank BJB KCP Mojokerto has implemented good credit assessment using the 5C principles with character and capacity as the bank's main assessment in minimizing credit risk. This research suggests banks improve the risk analysis system, strengthen risk management, strengthen collaboration between the credit assessment department and the risk management department, and provide education to creditors regarding the systematics of credit applications.